The effect of genistein supplementation on performance and antioxidant status of Japanese quail under heat stress - Onderci, M; Şahin, Kazım; Şahin, Nurhan; Gursu, MF; Doerge, D; Sarkar, FH; Küçük, Ömer (Taylor & Francis Ltd, 2004)
Genistein, a phytoestrogen found in soybeans, is a powerful antioxidant. We evaluated the effects of genistein supplementation on performance, carcass characteristics, levels of malondialdehyde (MDA), homocysteine, vitamins C, E, A in Japanese quail (Coturnix coturnix japonica) exposed to high ambient temperature of 34degreesC. Two hundred and forty Japanese quails (10 d old) were randomly assigned to eight treatment groups consisting of 10 replicates of three birds. The birds were kept in an environmental controlled room either for 24 h/d at 22degreesC with (thermoneutral, TN groups) or for 16 h/d at 22degreesC and for 8 h/d (09.00 am to 05.00 pm) at WC (heat stress, HS groups). Birds were fed either a basal (control) diet (TN and HS) or the basal diet supplemented with 200, 400 or 800 mg of genistein per kg of diet. Heat exposure decreased birds' performance when basal diet was fed. Increase in feed intake and body weight, and improvement of feed efficiency and carcass traits were found in genistein-supplemented quails reared under heat stress conditions. Growth rate and feed efficiency improved in quails reared under thermo-neutral conditions as well. Concentration of serum vitamins C, E, and A increased in supplemented birds reared at high temperature, while non-significant changes occurred in TN groups. With genistein supplementation homocysteine levels in serum and MDA levels in serum and liver decreased in all birds of both TN and HS groups. Effects of genistein were relatively greater in heat-stressed quails than in quails kept under thermo-neutral conditions. Results of the present study suggest that supplementation with genistein can be considered to be protective by reducing the negative effects of oxidative stress induced by heat stress in quail.
Keywords: genistein; heat stress; peroxidation; performance; quail